A Nearly Interference-Free and Depth-Resolution-Configurable Time-of-Flight System Based on a Mega-Pixel Vertical Avalanche Photodiodes CMOS Image Sensor - Shota Yamada; Motonori Ishii; Shigetaka Kasuga; Masato Takemoto; Hiromu Kitajima; Toru Okino; Yusuke Sakata; Manabu Usuda; Yugo Nose; Hiroshi Koshida; Masaki Tamaru; Akito Inoue; et al. (IEEE Open Journal of Circuits and Systems, 2022)
We present a long range (~250 m) time-of flight (TOF) system with suppressed (nearly-free) mutual-interference. The system is based on a $1296×960$ pixels vertical avalanche photodiodes (VAPD) CMOS image sensor (CIS). Real-time long-range 3D-imaging with 30 fps speed (450 fps for 2D imaging) is demonstrated. Designs and operation principles of the core circuits, i.e., a photon counting circuit and a global shutter driver, are fully described. The ranging method is based on a sub-range synthesis (SRS) where a range is set by the phase of exposure pulses with respect to that of the light source of the system. The depth resolution is configurable in that the minimum sub-range width limited by the light source pulse width of 10 ns or 1.5 m can be reduced to a 10 cm by introducing an indirect-TOF operation. Furthermore, by employing a random flight timing (RFT), mutual-interference in raw signal level is suppressed by 35 dB when 2 cameras are simultaneously operated. By simulation, the present system is estimated to be tolerant up to a case of 27 cameras operation.